2014
DOI: 10.12785/jtte/020104
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers’ Perceptions of Sources of Teaching Practice-Related Anxieties

Abstract: Teaching practice is a very vital component of teacher programme. This study examined student teacher"s perceptions of the source of teaching practice related anxieties. The student teacher"s source of anxieties questionnaire (STSAQ) was used for data collection. Two hundred and seventy-seven undergraduate students of the Faculty of Education in the University of Benin in their penultimate and final years who were on teaching practice in the 2011/2012 session in secondary schools across the country took part i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Specifically, in relation to the third research question and professional learning aspects of the ICT plan and improvements needed at the system level, some of the relevant training in using ICT for administrative purposes had been implemented by Papuan key personnel. However, despite research indicating the importance of training in ICT which involves frequency of practice for teachers and time for a mindset shift from teacher-centered to student-centered learning (Allen et al, 2018;Danner, 2014;Harendita, 2013), it seemed that other essential ICT professional learning, such as in using ICT for curriculum purposes, did not occur. Given insufficient ICT training and use, teachers and principals did not generally have high levels of technical skills on computers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in relation to the third research question and professional learning aspects of the ICT plan and improvements needed at the system level, some of the relevant training in using ICT for administrative purposes had been implemented by Papuan key personnel. However, despite research indicating the importance of training in ICT which involves frequency of practice for teachers and time for a mindset shift from teacher-centered to student-centered learning (Allen et al, 2018;Danner, 2014;Harendita, 2013), it seemed that other essential ICT professional learning, such as in using ICT for curriculum purposes, did not occur. Given insufficient ICT training and use, teachers and principals did not generally have high levels of technical skills on computers.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond attitudes, teacher and student ICT use in the classroom is influenced by pedagogical practices, teacher training, and computer familiarity (Mwendwa, 2017). Teachers need to build their skills through frequent ICT use and practice which leads to changes in pedagogy, with professional learning occurring that supports teachers in confidence building (Danner, 2014) and with the government "focusing more on how critical pedagogy can be fostered through the use of ICT" (Harendita, 2013 p. 207). Mailizar and Fan's (2019) research in Indonesia with secondary maths teachers similarly indicates the need for building knowledge of ICT relevant to the subject area and knowledge of relevant pedagogical practices using ICT.…”
Section: Background Ict Attitudes and Professional Developmentmentioning
confidence: 99%
“…Furthermore, personality factors, precisely speaking, neurological personality, underlie much of the anxiety of pre-service teachers. However, it is noteworthy that neither gender differences nor academic level differences in terms of student teachers' anxiety were found in Danner's (2014) study, which studied two hundred and seventy-seven undergraduate students of the Faculty of Education in a University from Nigeria. The results suggest that anxiety is a reality student teachers must face during the teaching practicum although individual difference in terms of FLTA remains an undetermined issue.…”
Section: Pre-service Efl Teacher Anxietymentioning
confidence: 89%
“…However, Arslan & Ilin (2018) commented that the experiences of student-teachers during practicum direct to changes their concerns about teaching. Danner (2014) suggested that it is better to have intervention programs for student-teachers' teaching practice-related anxieties about improving teacher preparation program.…”
Section: Murraymentioning
confidence: 99%